PROGRAMA DE DESENVOLVIMENTO DE FORNECEDORES DO ESTADO DO MARANHÃO (PDF-MA): uma estratégia de sucesso? - HOSSOÉ, Heric Santos (2018)
In this thesis, a thorough research is aimed at evaluating the impacts of the adoption of the Supplier Program of the State of Maranhão (PDF-MA), especially in terms of turnover and job creation. For this it is carried out from the historical contextualization going from the most general to the most specific, contemplating from the productive restructuring to the formulation and implementation of the program. Next, the theoretical framework and the categories developed in the research are discussed, notably sustainable development and work. Finally, the field research is carried out, in which, based on qualitative-quantitative techniques, three dimensions are explored, in six strands, so that it is possible to evaluate the effectiveness of the PDF-MA, bringing the surface beyond the appearance and of what is propagandized, seeking in synthesis the essence of the phenomenon, now seen by a new prism.